Analisis Metode Penerangan Hadith Berʻillah Dalam Sahih Muslim Menurut Ḥamzah Al-Malyabārī: Analysis Method of Explaining Hadith Al-ʻIlal In Sahih Muslim According to Ḥamzah Al-Malyabārī - Mohd Rokhibi, Ibrahim Adham; Ahmad, Khadher (Online Journal of Research in Islamic Studies, 2022)
Ṣaḥīḥ Muslim is one of the greatest manuscript in Hadith and studies of transmitter. Many researches had come out that amid methodology of Imam Muslim, the most significant one is to accommodate the authentic hadith in early chapter. However, Imam Muslim's method towards compilation of authentic hadith in his Ṣaḥīḥ is various, and it has a very high purpose and intellectual value to explain the existense of deficiencies in the text or the chain of hadith (ilal hadith). Starting from that, this article aims to analyze the method of explanation of ilal hadith in Ṣaḥīḥ Muslim according to Ḥamzah al-Malyabārī. The analysis was conducted with reference to the books of ʻilal as well as studies related to the methodology of Ṣaḥīḥ Muslim. The result of this research can clarify the community's misunderstanding of this book and can be used by current hadith researchers in interacting with the hadiths of Ṣaḥīḥ Muslims.